2016
DOI: 10.18632/oncotarget.10596
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial transplantation attenuates hypoxic pulmonary hypertension

Abstract: Mitochondria are essential for the onset of hypoxia-induced pulmonary vasoconstriction and pulmonary vascular-remodeling, two major aspects underlying the development of pulmonary hypertension, an incurable disease. However, hypoxia induces relaxation of systemic arteries such as femoral arteries and mitochondrial heterogeneity controls the distinct responses of pulmonary versus femoral artery smooth muscle cells to hypoxia in vitro. The aim of this study was to determine whether mitochondrial heterogeneity ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 35 publications
(62 reference statements)
1
26
0
1
Order By: Relevance
“…Mt isolated from BM-MSCs were incorporated into injured renal tubules in vivo 1 d after the administration of Mt, whereby they induced histological improvements of proximal tubules in STZ rats within 3 d. According to previous reports, most of the intravenously administered Mt were trapped in the lungs and did not distribute to the kidneys 53 . From this result, we considered that it is difficult to assess the effect of MSC-derived isolated Mt on kidneys by systematic intravenous administration.…”
Section: Discussionmentioning
confidence: 99%
“…Mt isolated from BM-MSCs were incorporated into injured renal tubules in vivo 1 d after the administration of Mt, whereby they induced histological improvements of proximal tubules in STZ rats within 3 d. According to previous reports, most of the intravenously administered Mt were trapped in the lungs and did not distribute to the kidneys 53 . From this result, we considered that it is difficult to assess the effect of MSC-derived isolated Mt on kidneys by systematic intravenous administration.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial transplantation strategies based on the systemic injection of isolated functional mitochondria, stem cells, or EVs still do not possess a specificity of delivery and will affect a variety of cells, such as blood cells and vessel-rich organs such as the lung and liver. Previously, it was shown that the intravenous administration of isolated mitochondria caused the mitochondria to become trapped in the lungs ( Zhu et al, 2016 ), while the therapeutic efficacy of mitochondrial transplantation for the treatment of tissue injury or mitochondria-associated disorders will benefit from the targeted delivery of mitochondria into a specific tissue or organs. Due to the inherited characteristics of mitochondrial diseases and the presence of defective mitochondria in every cell of an organism, specificity of mitochondrial delivery is not always strictly necessary.…”
Section: Mitochondrial Delivery Strategiesmentioning
confidence: 99%
“…To further investigate whether mitochondrial or non-mitochondrial COMP is responsible for VSMC identity, we performed mitochondrial transplantation as described previously 33 , 34 . The mitochondria were isolated from scrambled or COMP- silenced donor VSMCs and then transplanted into recipient mitochondria-deleted VSMCs treated with scrambled or COMP siRNA respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondria were transplanted as previously described 33 , 34 . To remove endogenous mitochondria, VSMCs at 80% confluence in culture were either maintained in DMEM as control or treated in DMEM supplemented with 110 µg/ml sodium pyruvate, 50 µg/ml uridine, and different concentrations of ethidium bromide (50, 100, or 200 ng/ml), respectively.…”
Section: Methodsmentioning
confidence: 99%